Patient-reported outcomes for patients with breast cancer undergoing radiotherapy: A single-center registry experience - Laughlin, Brady S.; Bhangoo, Ronik S.; Thorpe, Cameron S.; Golafshar, Michael A.; DeWees, Todd A.; Anderson, Justin D.; Vern-Gross, Tamara Z.; McGee, Lisa A.; Wong, William W.; Halyard, Michele Y.; Keole, Sameer R.; Vargas, Carlos E. (Frontiers in Oncology, 2022)
Background We present Patient-Reported Outcomes Version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) for patients undergoing adjuvant radiotherapy for breast cancer with curative intent. We describe the frequency and severity of PRO-CTCAE and analyze them with respect to dose fractionation. Methods Patients were included in this study if they were treated with curative intent for breast cancer and enrolled on a prospective registry. Patients must have completed at least one baseline and one post-radiation survey that addressed PRO-CTCAE. For univariate and multivariate analysis, categorical variables were analyzed by Fisher’s exact test and continuous variables by Wilcoxon rank sum test. PRO-CTCAE items graded ≥2 and ≥3 were analyzed between patients who received hypofractionation (HF) versus standard conventional fractionation (CF) therapy by the Chi-square test. Results Three hundred thirty-one patients met inclusion criteria. Pathologic tumor stage was T1–T2 in 309 (94%) patients. Eighty-seven (29%) patients were node positive. Two hundred forty-seven patients (75%) experienced any PRO-CTCAE grade ≥2, and 92 (28%) patients experienced any PRO-CTCAE grade ≥3. CF was found to be associated with an increased risk of grade ≥3 skin toxicity, swallowing, and nausea (all p < 0.01). HF (OR 0.48, p < 0.01) was significant in the multivariate model for decreased risk of any occurrence of PRO-CTCAE ≥3. Conclusions Our study reports one of the first clinical experiences utilizing multiple PRO-CTCAE items for patients with breast cancer undergoing radiation therapy with curative intent. Compared with CF, HF was associated with a significant decrease in any PRO-CTCAE ≥3 after multivariate analysis.